2018
DOI: 10.1007/s40089-018-0243-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the surface charge of silica nanoparticles on oil recovery: wettability alteration of sandstone cores and imbibition experiments

Abstract: Recently, inorganic nanomaterials have emerged as promising wettability modifiers to improve oil recovery. Among them, silica nanoparticles (SNPs) have gained a privileged place due to their outstanding properties. Several studies have reported the effectiveness of SNPs on this particular application. However, there is an increasing interest of understanding the parameters that may play an important role on oil recovery using nanofluids. The impact of particle size, particle concentration and types of nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This confirms the premise proposed by Omurlu et al [ 67 ] that the more negatively charged, diol-modified nanomaterials tend to adhere better to the pore walls that are coated by ferric oxide, which promotes more positive surface charge. The observation is also in agreement with Alvarez-Berrios et al [ 30 ], who proposed that due to this adhesion (NPs adhering to the rock surface), the mineral surface will be tuned towards more favorable wettability state. One reason to explain this effect is the exchange of the nanofluid forms a wedge-shaped thin film due to the existence of disjoining pressure.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This confirms the premise proposed by Omurlu et al [ 67 ] that the more negatively charged, diol-modified nanomaterials tend to adhere better to the pore walls that are coated by ferric oxide, which promotes more positive surface charge. The observation is also in agreement with Alvarez-Berrios et al [ 30 ], who proposed that due to this adhesion (NPs adhering to the rock surface), the mineral surface will be tuned towards more favorable wettability state. One reason to explain this effect is the exchange of the nanofluid forms a wedge-shaped thin film due to the existence of disjoining pressure.…”
Section: Resultssupporting
confidence: 91%
“…Hydrophilicity promotes a water-wet surface [ 28 ], while hydrophobic NPs have almost no impact on the wettability [ 29 ]. Alvarez-Berrios et al [ 30 ] investigated the effect of surface charge of silica NPs on the wettability alteration using Berea sandstone outcrops. The authors found through contact angle measurements that slightly negatively charged SiNPs reduced the contact angle from oil-wet to water-wet (106.3° to 74°).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the prominent role of zirconia NFs on the wettability alteration at 70 °C and 20 MPa and at low concentration was observed on the quartz surface. 47 Alvarez-Berrios et al 48 stated that the surface-modified silica NPs have a good impact on wettability alteration of a sandstone surface at higher concentrations of NPs. Similarly, Wang et al 49 disclosed that surface-modified TiO 2 NPs perform better than bare TiO 2 NPs in altering the wettability of the rock surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, instead of the mean diameter decreasing as the number of aqueous silica nanoparticles raises, the mean particle diameter increased initially then was reduced in the present study. Generally, silica nanoparticles have negatively charged surfaces due to the presence of siloxane and silanol groups on their surfaces [25].…”
Section: Results and Discussion Effect Of Silica Nanoparticles On The...mentioning
confidence: 99%